Towards a Typology for Understanding Mobile Phone Victimisation in South African High Schools - Lusinga, Shallen (Department of Information Systems, 2016)
Mobile victimisation is one form of cyber aggression that is increasing and affecting many young people today. While several studies on cyberbullying and cyber victimisation have been done, the focus on mobile victimisation has been limited. In addition, findings presented in earlier studies have been inconclusive, and there is limited theory development to enhance conceptualisation and general understanding of this form of aggression. Calls have, therefore, been made to investigate mobile aggression and victimisation further. The present study aims to create better understanding of the nature of mobile victimisation in South African high schools. This study will also identify significant factors that influence mobile victimisation. Through an extensive review of the literature and theoretical works on victimisation, the researcher was able to develop a mobile victimisation typology that would guide this research. This typology is based on the premise that the frequency of mobile phone use, the technological advancement of a mobile phone and the emotional attachment to a mobile phone are key predictors of mobile victimisation. In addition, it predicts that the extent to which victims contribute to their victimisation is dependent on the extent to which the victim engages in these predictors. The typology divides victims into three categories: (i) innocent victims (victims who do not contribute to their own victimisation), (ii) victims with low contribution (those who make limited contribution to their own victimisation), and (iii) victims with moderate to high contribution (those who contribute largely to their victimisation).